PENGENALAN PERBANKAN SYARIAH DAN INTERNALISASI AKAD-AKAD EKONOMI SYARIAH PADA BUMDES DESA KARANGSEGAR - Ainun Nuriah; Rafika Rahmawati; Fajri Ryan Isnandar; Siti Mardiah (LPPM Universitas Islam 45, 2023)
Village Owned Enterprises are instruments driving the macro economy at the village level based on local potential and local wisdom. The management of Village-Owned Enterprises can be a solution to advance and improve the village economy. The majority of Karangsegar villagers are Muslim, so the management of business activities should be in accordance with Islamic law. However, there are still many people who do not know about Islamic economics and are not interested in implementing Islamic economics. Therefore, the socialization of the introduction of Islamic banking and the internalization of Islamic economic contracts is very necessary. This study aims to provide an understanding of contracts in Islamic economics and explain related to the implementation of Islamic transactions in society to determine the understanding and interest of the community to use Islamic economics in carrying out their business activities. The implementation method used is the community education method which was attended by 6 BUMDES management. The collection of supporting data is carried out by field studies through interviews, observation and documentation. The results of this study indicate that Karangsegar village BUMDES have not implemented transactions with the sharia economy, so researchers provide results in the form of a sharia contract implementation model through contract internalization on Karangsegar village BUMDES products.